2012
DOI: 10.1007/s10059-012-2242-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiling Reveals an Unexpected Growth-Stimulating Effect of Surplus Iron on the Yeast Saccharomyces cerevisiae

Abstract: Iron homeostasis plays a crucial role in growth and division of cells in all kingdoms of life. Although yeast iron metabolism has been extensively studied, little is known about the molecular mechanism of response to surplus iron. In this study, expression profiling of Saccharomyces cerevisiae in the presence of surplus iron revealed a dual effect at 1 and 4 h. A cluster of stress-responsive genes was upregulated via activation of the stress-resistance transcription factor Msn4, which indicated the stress effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
(20 reference statements)
3
7
0
Order By: Relevance
“…The Snf complex is known to activate the general stress transcription factors Msn2 and Msn4 (18,19). Furthermore, iron has been shown to induce the transcription of MSN4, and it has been shown that there are Msn4/Msn2-binding sites on the CCC1 promoter (20). We confirmed that overexpression of MSN2 affects CCC1 transcription by measuring CCC1-lacZ activity in cells transformed with a plasmid containing MSN2 under the control of the ADH2 promoter.…”
Section: Msn2 and Msn4 Are Involved In Ccc1-dependent Iron Resistancesupporting
confidence: 68%
See 1 more Smart Citation
“…The Snf complex is known to activate the general stress transcription factors Msn2 and Msn4 (18,19). Furthermore, iron has been shown to induce the transcription of MSN4, and it has been shown that there are Msn4/Msn2-binding sites on the CCC1 promoter (20). We confirmed that overexpression of MSN2 affects CCC1 transcription by measuring CCC1-lacZ activity in cells transformed with a plasmid containing MSN2 under the control of the ADH2 promoter.…”
Section: Msn2 and Msn4 Are Involved In Ccc1-dependent Iron Resistancesupporting
confidence: 68%
“…In considering the downstream transcription factor(s) affected by activation of Snf1, we considered Msn2 and Msn4 as candidates based on published studies that showed that Msn2 and Msn4 were activated by Snf1 (27) and that Msn2/Msn4 activation resulted in increased iron-dependent growth and induction of CCC1 (20). We confirmed that Msn2 and Msn4 contributed to Snf1-mediated regulation of CCC1 transcription.…”
Section: Discussionsupporting
confidence: 58%
“…Remarkably, the Snf1 activation of CCC1 does not depend on Yap5 or ISC biogenesis, but utilizes Msn2 and Msn4 transcription factors and other unidentified regulatory factors (Li et al, 2017). Consistent with this, the msn2 msn4 double mutant is sensitive to iron and the Msn4 protein translocates to the nucleus in response to excess iron (Du et al, 2012;Li et al, 2017). Further studies are necessary to decipher how iron modulates the activity of the Snf1 kinase complex since no changes in Snf1 phosphorylation have been reported upon exposure to high iron.…”
Section: Regulation In Response To Iron Excessmentioning
confidence: 78%
“…This category had similar relevance when SDP8 cells were treated for 24 h with the antibiotic ( p -value: 3.77e-05). These expression patterns recall the transcriptional changes described under iron-surplus conditions, controlled by the Aft1and Aft2 transcription factors [ 25 ]. In fact, there is a good correlation (R 2 = 0.68) between the expression changes of the genes down-regulated by incubation of SDP8 cells with doxycycline for 24 h and the set of Aft1-dependent iron transport genes [ 26 ] (Fig.…”
Section: Resultsmentioning
confidence: 56%